IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN BAHASA INDONESIA MATERI TEKS NONFIKSI - Vita Ella Yudiawati; Dzarna; Astri Widyaruli (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to explore the implementation of differentiated learning in the Indonesian language subject, focusing on nonfiction text material in class XII-7 of SMAN Pakusari. The research employs a descriptive qualitative approach to analyze how differentiated learning strategies respond to diverse student needs, learning styles, and preferences in summarizing nonfiction articles. Data were collected through questionnaires, observations, and documentation. Students were offered three summarizing methods—oral presentation, written summary, and infographic mind map—based on their individual learning preferences. The findings show that most students preferred using infographic mind maps, reflecting a visual learning inclination, followed by oral and written formats. Each method facilitated students in expressing their comprehension effectively, contributing to higher engagement and deeper understanding. The implementation encouraged collaborative learning, improved critical thinking, and empowered students to present ideas in ways that suited their strengths. The study concludes that differentiated instruction significantly enhances student motivation, learning outcomes, and 21st-century skills development. It highlights the teacher’s role as a responsive facilitator who adapts instructional content, processes, and products to accommodate individual student profiles. The research emphasizes the potential of differentiated learning to create inclusive, meaningful, and flexible classroom experiences that align with contemporary educational demands.